Penerapan Senam Aerobic Low Impact pada Perempuan Perimenopause untuk Mempertahankan Massa Otot dan Mengurangi Fatigue - Amelia Wanda Putri; Shabrina Auliya Syifa Salsabila; Minhatul Maula Tsunaiya; Idriani Idriani; Irna Nursanti; Irma Permata Sarif (Lembaga Pengembangan Kinerja Dosen, 2026)
Perimenopause is an important phase in a woman's life characterized by extensive hormonal changes as the ovaries gradually lose their function. During this period, the body experiences significant hormonal fluctuations, particularly a decrease in estrogen and progesterone production, which can cause various physical discomforts such as fatigue. One way to overcome fatigue is through low-impact exercise. This exercise is a light, safe activity that can improve physical fitness and enhance the body's endurance, thereby potentially reducing fatigue levels in perimenopausal women. This study used a descriptive method with a case study approach conducted on two perimenopausal women, Mrs. T and Mrs. N. The results of the nursing care showed that after six sessions of low-impact exercise over two weeks, the fatigue levels of both respondents decreased, as evidenced by their Fatigue Assessment Scale (FAS) scores. Mrs. S's FAS score decreased from 28 to 23, while Mrs. N's decreased from 30 to 27. The symptoms experienced by Mrs. T decreased on the third day and further decreased on the sixth day. For Mrs. N, symptoms decreased on the third day and further decreased on the fifth day. The results of this study indicate that low-impact exercise is effective as an intervention for fatigue issues in perimenopausal women.